2017
DOI: 10.7754/clin.lab.2017.170601
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Serum Procalcitonin in Early Infection after Internal Fixation for Traumatic Fracture

Abstract: The serum PCT level can be used as an early diagnostic indicator of infection after internal fixation for traumatic fracture. The combined use of PCR and CRP levels can increase the sensitivity of detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The study was conducted on a large, well defined, nationwide cohort of COPD patients with complete data available on prescription of medication and hospital admissions [17][18][19][20].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The study was conducted on a large, well defined, nationwide cohort of COPD patients with complete data available on prescription of medication and hospital admissions [17][18][19][20].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In short, when preoperative ESR and CRP level are abnormally elevated, their diagnostic value is limited [ 22 ]. The value of PCT combined with CRP in the detection of early postoperative infection is higher than that of CRP when tested alone [ 23 ]. Therefore, we can use CRP and ESR combined with PCT to improve the diagnostic sensitivity for infection after IF.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis, performed by Vouloumanou et al, 7 suggests that PCT has great diagnostic value after the first 48 h of life. Meanwhile, Zhao et al 8 found that PCT was useful for the early diagnosis of severe infection but had limited value in the diagnosis of mild infection. CRP is an acute, time-phase protein that begins to rise 4–6 h after bacterial infection and usually reaches an effective threshold after 24–48 h. However, CRP fluctuates greatly in the first 3 days after birth, so errors arise in the diagnosis of neonatal infection based on CRP alone.…”
Section: Introductionmentioning
confidence: 99%